AB0670 A cross-sectional study of the disease activity and damage index of systemic lupus erythematosus (SLE) patients in two urban tertiary referral centres. (23rd January 2014) - Ding, H.J.; Hussein, H.
Abstract : Background: SLICC/ACR Damage Index (SDI) and Systemic Lupus Erythematosus Disease Activity Index (SLEDAI) are internationally validated indices for assessing disease activity and cumulative damage. There have not been many studies looking into characteristics of disease activity and damage in SLE patients, especially in the South-east Asian region. Objectives: We wanted to assess disease activity and damage in our cohort and to evaluate if there were any associations of activity and damage with race, drug therapy, income level, age and duration of therapy. Methods: The study was carried out in 2011 in two rheumatology referral centres in Klang Valley: Putrajaya and Klang. 119 consecutive patients attending the outpatient lupus clinics were studied. The patients fulfilled the American College of Rheumatology criteria for SLE. Disease activity was assessed using the SLEDAI while damage was assessed using SLICC/ACR Damage Index. Data on disease duration, income level, hydroxychloroquine (HCQ), glucocorticoid (GC) and cyclophosphamide (CYC) use were also collected using a proforma. Results: The mean (SD) age of our patients was 34.1 years (11.3). 97.5% were females. 77.3% were Malays. 62.2% were in the middle income bracket. The median (IQR) SLEDAI score was 1.0 (3), with a range of 0 to 18. The most frequent manifestations were found in immunologic (55.8%) and mucocutaneous activity (19.3%). The median (IQR) DI score was 0.0 (1) with a range of 0 to 7. The most common organ involvement was ocular (26.9%), neuropsychiatric (19.2%) and renal (19.2%). 93.3% were on HCQ, 79.8% were on GC and 17% had ever received CYC. Damage was associated with age ( p 0.026) and disease duration ( p 0.016). Disease activity was negatively associated with age ( p 0.04, r -0.819). Disease activity and damage were not associated with drug therapy, level of income or race. There was also no correlation between activity and damage. Our damage scores were similar to several reported studies but our activity scores were relatively lower. Conclusions: This study agrees with previous studies that disease damage was associated with age and disease duration and that there was no correlation between disease activity and damage. Our study found that disease activity was negatively associated with age. Our lower damage scores could reflect the fact that our population was younger and had shorter disease duration. Our low disease activity scores could be explained by adequate disease control and benign disease. References: Yee CS, Hussein H, Skan J, Bowman S, Situnayake D, Gordon C et al. Association of damage with autoantibody profile, age, race, sex and disease duration in systemic lupus erythematosus. Rheumatology 2003;42:276-9 Gladman DD, Urowitz MB, Goldsmith C et al. Assessment of the reliability of the SLICC/ACR damage index for SLE. Arthritis Rheum 1997;40:809-13 Gladman D, Urowitz M, Ong A et al. Lack of correlation among 3 outcome measures in SLE: disease activity, damage and quality of life. Clin Exp Rheumatol 1996;14:305-8 Hanly JG. Disease activity, cumulative damage and quality of life in systemic lupus erythematosus: results of a cross-sectional study. Lupus 1997;6:243-7 Disclosure of Interest: None Declared